(untitled) (Revista de Ciencias de Seguridad y Defensa, 2023)
Protection against denial of service attacks is crucial in cyberspace to ensure the availability of services and preserve the integrity of systems. This study focused on analyzing Slowloris attacks in a virtualized environment. An Ubuntu server running Apache was used to host a vulnerable website. Additionally, attacks were carried out with two different Slowloris tools and then security measures were implemented to evaluate their effectiveness in mitigating these attacks. The results highlight the importance of adopting proactive security measures to protect virtual systems against cyber threats. This improves resistance to Slowloris-type denial-of-service attacks in a virtualized environment.